The effects of low-carbohydrate diet on glucose and lipid metabolism in overweight or obese patients with T2DM: a meta-analysis of randomized controlled trials - Tian, Wende; Cao, Shuyu; Guan, Yongxin; Zhang, Zihao; Liu, Qiyu; Ju, Jianqing; Xi, Ruixi; Bai, Ruina (Frontiers in Nutrition, 2025)
BackgroundThe dual burden of Type 2 Diabetes Mellitus (T2DM) and obesity is a critical public health issue. Low-carbohydrate diets have emerged as a potential intervention, yet clinical evidence remains inconclusive.PurposeThis meta-analysis assesses the impact of low-carbohydrate diets on metabolic profiles in overweight or obese T2DM patients, aiming to guide clinical practice.MethodsA systematic review identified randomized clinical trials (RCTs) comparing low-carbohydrate diets to control diets in T2DM patients from PubMed, Embase, and the Cochrane Library databases up to April 2023.ResultsSeventeen RCTs, encompassing 1,197 participants, demonstrated that low-carbohydrate diets significantly improved HbA1c levels and fasting plasma glucose (mean difference [MD] = −0.36, 95% CI −0.44 to −0.29, p < 0.00001; MD = −10.71, 95% CI −14.39 to −7.03, p < 0.00001). They also reduced triglycerides and increased HDL cholesterol (MD = −19.91, 95% CI −28.83 to −10.99, p < 0.00001; MD = 2.49, 95% CI 1.07–3.91, p = 0.0006), without affecting LDL and total cholesterol. Weight loss, reduced BMI, lower diastolic blood pressure, and decreased waist circumference were additional benefits.ConclusionLow-carbohydrate diets may enhance glycemic control and lipid profiles in overweight or obese T2DM patients, warranting consideration in T2DM management. However, the variability in diet definitions and methodologies underscores the necessity for further research to standardize dietary guidelines and evaluate long-term effects.